Does The Subsidized Rice Program Successfully Alleviate Poverty? (a Case Study Central Java Province) - Aris Eko Purnomo; Bambang Supriyono; MR. Khairul Muluk (Sekolah Pascasarjana Universitas Brawijaya, 2015)
This research tried to find out problems surrounding the implementation of the subsidized rice program using qualitative method by observing the context of policy (including power and strategies, characteristic of authorities, and compliance). The program is designed to avoid poor people from severe hunger by providing extremely cheap rice by obeying its principles â€˜6Psâ€ (Precise in Quantity, Quality, Price, Target, Time and Administration), that is why the research focuses to observe the context of policy, since those principles are related to societyâ€™s conditioninstead ofthe policy (content). In fact, more than 28 million Indonesian still struggles to escape from poverty trap. It means that there are problems during the implementation, so that the research reveals that the principles were not obeyed completely and failed to help poor. Therefore, it gives critical advices to boost the program, such as improving database accuracy, tightening the evaluation, and strengthening the double impacts.Keywords:hunger, poverty alleviation program, poor, raskin, subsidized rice program